Smoldering ceramic-based synergistic denitration and hydrocarbon removal catalyst as well as preparation method and application of smoldering ceramic-based synergistic denitration and hydrocarbon removal catalyst
By using the ceramic particle carrier made of drifting beads and AL2O3 mixtures, combined with the composite oxide activity components of CEO2 and CUO, to prepare a yin -burning ceramic foundation coordinated denitrification of hydrocarbon catalysts, solving the disposal of staining and dirty, smoke, and smoke gas disposal and The lack of low -temperature denitration catalytic activity has achieved efficient low -temperature catalytic and smoke purification effects.
Patent Information
- Application Number
- CN202411505627.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, the flue gas treatment effect during the smoldering process of printing and dyeing sludge is poor, and the catalytic activity of the low-temperature denitrification catalyst is insufficient, resulting in environmental protection and economic problems.
Ceramic particles made of drifting beads and AL2O3 are used as carriers, and composite oxides of CEO2 and CUO are used as active components. Coordinated denitration dehydrocarbon catalyst.
The catalyst is efficiently catalytic to generate N2 at low temperature. It does not require additional reducing agents. It can coordinate the removal of hydrocarbon compounds and nitrogen oxides in the flue gas, and improve the mechanical life and catalytic performance of the catalyst.
Smart Images

Figure CN119368192A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a smoldering ceramic-based synergistic denitration and decarbonization catalyst, and belongs to the field of industrial flue gas purification. Background Art
[0002] At present, there are two main problems with biomass combustion technology in my country. The first is the economic problem. In addition to the high cost of biomass collection, transportation and pretreatment, the high solid phase temperature during biomass combustion causes compounds such as K, Na, and Cl to escape, forming sticky fouling in the heat exchanger, resulting in low heat exchange efficiency, and causing fuel to coke and slag, resulting in high equipment failure rate and high operation and maintenance costs. The second is the environmental problem. Biomass combustion produces VOCs, C x H y 、NO x , solid particles, solid slag, etc. emissions are high.
[0003] SCR method is the most commonly used NO x Removal method: The core technology of SCR method is mainly focused on the research and development of new denitration catalysts. Currently, commercial catalysts are mainly divided into two categories: vanadium-based catalysts and rare earth-based catalysts. However, commercial vanadium-based catalysts still have some inevitable defects, such as poor low-temperature activity, volatility and biological toxicity of V2O5, which seriously hinder their further development in practical applications. Therefore, it is very important to prepare an environmentally friendly catalyst that overcomes the above shortcomings.
[0004] Among the existing low-temperature denitration patents, patent CN201510488728.8 uses Cr2O3 and V2O5 as active components, NiSO4 as an auxiliary agent, and TiO2 as a carrier to prepare a low-temperature denitration catalyst, which improves the chemical adsorption capacity of NH3 at low temperatures, thereby improving the catalyst activity, while reducing the conversion rate of SO2 / SO3 and extending the service life of the low-temperature denitration catalyst. Patent CN201811654451.1 prepares a ruthenium-based ultra-low temperature denitration catalyst by segmented impregnation and roasting, achieving good denitration effect under ultra-low temperature conditions, significantly improving anti-poisoning performance, and having the advantages of long service life. Patent CN201710773182.X obtains a low-temperature denitration catalyst by loading metal oxides with nitrogen-doped graphene, which has a good denitration effect under low temperature conditions and can effectively combat sulfur dioxide. Although the above catalysts achieve high catalytic activity at low temperatures, due to the presence of V or precious metals, the catalysts are expensive and not suitable for large-scale industrial applications. On the other hand, patent CN201610435984.5 discloses a method for treating flue gas from biomass pellet combustion, which only removes particulate matter in the flue gas and does not mention the treatment of incompletely burned gases. Patent CN201910522702.9 discloses a method for treating smoldering organic solid waste and purifying flue gas, which uses the addition of fuel gas to treat the flue gas. However, in small batch equipment, it is difficult to implement the regulation of the mixture of fuel gas and non-steady-state flue gas. Summary of the invention
[0005] The purpose of the present invention is to address the current problems of smoke disposal during the smoldering of printing and dyeing sludge and the insufficient catalytic activity of low-temperature denitrification catalysts, and to propose a preparation method and application of a smoldering ceramic-based synergistic denitrification and dehydrogenation catalyst.
[0006] A smoldering ceramic-based synergistic denitrification and decarbonization catalyst, the catalyst uses ceramic particles made of a mixture of floating beads and Al2O3 as a carrier, a composite oxide of CeO2 and CuO as an active component, and dilute hydrochloric acid as an acidifier. The catalyst is prepared by a hydrothermal filling-high temperature roasting-low temperature hydrothermal acidification-low temperature roasting method; based on the mass of the carrier, the mass percentage of the active component is 1-10%, the mass ratio of the floating beads to Al2O3 in the carrier is 1:0.1-5, and the mass ratio of CeO2 to CuO in the active component is 1:0.1-5.
[0007] In the above catalyst: based on the mass of the carrier, the mass percentage of the active component is 3-5%, the mass ratio of the floating beads and Al2O3 in the carrier is 1:0.3-1, and the mass ratio of CeO2 and CuO in the active component is 1:0.5-1.
[0008] A method for preparing the above-mentioned catalyst, the method for preparing the catalyst is as follows:
[0009] (1) Preparation of ceramic particle carrier
[0010] Weigh aluminum salt, deionized water and pretreated floating beads, mix them and place them in a hydrothermal stirring kettle, filter and dry them after hydrothermal reaction, and then place them in a high-temperature tube furnace for calcination to obtain a ceramic particle carrier;
[0011] (2) Modification of ceramic particle carrier
[0012] The ceramic particle carrier obtained in step (1), deionized water and dilute hydrochloric acid are mixed and placed in a hydrothermal reaction kettle, and after the hydrothermal reaction, the mixture is filtered and dried to obtain a modified ceramic particle carrier;
[0013] (3) Preparation of Catalyst
[0014] Weigh cerium salt and copper salt, dissolve them in deionized water and stir evenly to obtain an active component precursor mixed solution, then place the modified ceramic particle carrier obtained in step (2) in the active component precursor mixed solution, immerse and dry and calcine to obtain a smoldering ceramic-based synergistic denitrification and decarbonization catalyst.
[0015] In the above treatment method, the floating beads pretreatment method is to add fly ash into deionized water, stir and let it stand, filter and dry the ash floating on the surface of the deionized water by overflow, and then continue to add the filtered and dried ash into deionized water, stir and let it stand, and obtain the ash on the surface of the deionized water by overflow, and filter and dry for the second time to obtain the pretreated floating beads.
[0016] In the above treatment method: the temperature of the hydrothermal reaction described in step (1) is 140-160°C, and the time of the hydrothermal reaction is 6-12 hours; the stirring rate during the hydrothermal reaction is 40-60 r / min; the drying temperature is 70-100°C, and the drying time is 4-8 hours; the calcination temperature is 1200-1400°C, and the calcination time is 8-16 hours.
[0017] In the above treatment method: the mass ratio of the ceramic particle carrier, deionized water and dilute hydrochloric acid in step (2) is 1:40-60:3-5, and the dilute hydrochloric acid is a hydrochloric acid solution with a mass fraction of 2-10%;
[0018] The temperature of the hydrothermal reaction in step (2) is 100-120° C., and the time of the hydrothermal reaction is 1-2 hours; the temperature of the drying is 80-100° C., and the time of the drying is 4-8 hours.
[0019] In the above treatment method: the cerium salt described in step (3) is cerium nitrate hexahydrate or cerium chloride hexahydrate, and the copper salt is copper chloride or copper nitrate.
[0020] In the above treatment method: the drying temperature in step (3) is 80-100° C., and the drying time is 3-6 hours; the roasting temperature is 500-600° C., and the roasting time is 2-4 hours.
[0021] In the technical solution of the present invention, the catalyst is used in the treatment of flue gas during the smoldering of printing and dyeing sludge. Further, the treatment of the flue gas is the coordinated catalytic purification of hydrocarbons and nitrogen oxides.
[0022] The experimental conditions for evaluating the activity of the catalyst of the present invention are as follows: 1 mL of a 40-60 mesh catalyst is taken and poured into a quartz tube with an inner diameter of 8 mm, the quartz tube is placed in a tubular furnace, and the actual temperature of the catalytic reaction is adjusted by controlling the heating temperature of the tubular furnace. Intake gas components: NO (500 ppm), CH4 (500 ppm), O2 (11 vol.%), and the rest are N2, the total gas flow rate is 500 mL / min, the temperature is controlled at 120-300°C, and it stays stable for 30 minutes every 30°C. The NO concentration is tested using a Laoying 3021 portable carbon emission monitor, and the NO conversion rate is 100% after 3 minutes at 180-270°C.
[0023] Beneficial effects:
[0024] The catalyst prepared by the present invention can efficiently catalytically reduce NO to generate N2 at low temperature, and there is no need to spray ammonia or urea and other reducing agents into the flue gas, and only hydrocarbons (CH4 is used as an example for the catalyst performance evaluation) generated during the smoldering of printing and dyeing sludge are used as reducing agents. Compared with the prior art, the catalyst uses a mixture of floating beads extracted from fly ash of coal-fired power plants and ceramic particles made of alumina as carriers, which can not only make full use of a large amount of domestic fly ash resources and realize the high value-added resource utilization of fly ash, but also the extracted floating beads have the characteristics of light weight, high strength and wear resistance, and have anti-wear effect on smoke particles in the flue gas during the smoldering process, which can improve the mechanical life of the catalyst; the main components of the floating beads are silicon dioxide and aluminum oxide. In the present invention, the aluminum oxide is filled into the hollow floating beads by a hydrothermal filling method, which can further improve the surface acidity of the carrier by using the Tanabe rule, thereby promoting the improvement of catalytic performance, and at the same time, the ceramic particle carrier prepared by high-temperature calcination can improve the physical strength of the catalyst, and finally improve the mechanical life of the catalyst. In addition, ceramic carrier particles have the advantages of being light and strong, but they also have the disadvantage of low water absorption, which makes it difficult for the active components to be evenly loaded on the carrier surface and the bonding strength between the active component particles and the carrier is also low. Therefore, the present invention utilizes a low-temperature hydrothermal acidification method to slightly corrode the surface of the ceramic particle carrier to form a granular surface, thereby increasing the water absorption rate of the carrier and ultimately enhancing the bonding strength between the active component and the carrier surface. Finally, during the smoldering process of printing and dyeing sludge, hydrocarbons such as CH4 and nitrogen oxides will be produced, and CeO2 has excellent redox properties, while CuO has excellent oxidation properties. Therefore, CuO can adsorb and oxidize CH4 into reducing intermediate species, and CeO2 reacts the reducing intermediate species with NO to ultimately synergistically catalyze C xH y and NO x .
[0025] Therefore, the catalyst prepared by the present invention is not only environmentally friendly, but also can synergistically catalytically remove hydrocarbons and nitrogen oxides in the smoldering flue gas of printing and dyeing sludge at low temperature, and is conducive to the high value-added resource utilization of fly ash from coal-fired power plants, and has important economic and social effects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the SEM image of the catalyst prepared in Example 1;
[0027] Figure 2 This is the SEM image of the catalyst prepared in Comparative Example 1;
[0028] Figure 3 It is the NO efficiency diagram of the catalysts prepared in Examples 1, 2 and Comparative Example 1; DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with examples. The examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operating processes are given, but the protection scope of the present invention is not limited to the following examples.
[0030] Example 1
[0031] (1) Preparation of ceramic particle carrier
[0032] Weigh 20g of fly ash, add it to 1000g of deionized water, stir and stand for 60min, add deionized water to achieve overflow, filter out the ash floating on the surface of the deionized water and place it in an oven at 80°C for 8h, then continue to add the filtered and dried ash to 10g of deionized water, stir and stand, add deionized water to achieve overflow to obtain the ash on the surface of the deionized water, filter it twice and place it in an oven at 80°C for 8h; repeat the above steps 10 times to obtain 2g of floating beads; weigh 1.57g of aluminum chloride, 94.20g of deionized water and 2g of floating beads, mix them and place them in a hydrothermal stirring kettle, hydrothermally react at 140°C for 12h at a stirring rate of 40r / min, filter it, dry it at 80°C for 8h, and then place it in a high-temperature tubular furnace and calcine it at 1200°C for 16h to obtain a ceramic particle carrier;
[0033] (2) Modification of ceramic particle carrier
[0034] Weigh 2.5 g of the ceramic particle carrier obtained in step (1), 100 g of deionized water, and 7.5 g of 5% by mass dilute hydrochloric acid, mix them in a hydrothermal reactor, perform hydrothermal reaction at 100° C. for 2 h, filter, place in an oven at 80° C. and dry for 8 h to obtain a modified ceramic particle carrier;
[0035] (3) Preparation of Catalyst
[0036] 0.061 g of cerium chloride hexahydrate and 0.034 g of copper chloride were weighed and dissolved in 2.44 g of deionized water and stirred to obtain an active component precursor mixed solution. Then 2 g of the modified ceramic particle carrier prepared in step (2) was placed in the active component precursor mixed solution. After impregnation, it was dried at 80°C for 6 h and then calcined at 500°C for 4 h to obtain a smoldering ceramic-based synergistic denitrification and dehydrogenation catalyst (morphology see Figure 1 );
[0037] Based on the mass of the carrier, the mass percentage of the active component is 3%, the mass ratio of the floating beads and Al2O3 in the carrier is 1:0.3, and the mass ratio of CeO2 and CuO in the active component is 1:0.5.
[0038] (4) Catalytic activity test
[0039] Take 1mL of 40-60 mesh catalyst and pour it into a quartz tube with an inner diameter of 8mm. Place the quartz tube in a tube furnace and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), CH4 (500ppm), O2 (11vol.%), and the rest are N2. The total gas flow rate is 500mL / min. The temperature is controlled at 120-300℃, and stays stable for 30min every 30℃. The NO concentration is tested using Laoying 3021 portable carbon emission monitor. At 180-270℃, the NO conversion rate is 100% after 3min (see specific data). Figure 3 ).
[0040] Example 2
[0041] (1) Preparation of ceramic particle carrier
[0042] Weigh 20g of fly ash, add it to 2000g of deionized water, stir and stand for 120min, add deionized water to achieve overflow, filter out the ash floating on the surface of the deionized water and place it in an oven at 100°C for 4h, then continue to add the filtered and dried ash to 20g of deionized water, stir and stand, and add deionized water to achieve overflow to obtain the ash on the surface of the deionized water, filter it twice and place it in an oven at 100°C for 4h; repeat the above steps 10 times to obtain 2g of floating beads; weigh 8.36g of aluminum nitrate, 334.40g of deionized water and 2g of floating beads, mix them and place them in a hydrothermal stirring kettle, hydrothermally react at 160°C for 6h at a stirring rate of 60r / min, filter it, dry it at 100°C for 4h, and then place it in a high-temperature tubular furnace and calcine it at 1400°C for 8h to obtain a ceramic particle carrier;
[0043] (2) Modification of ceramic particle carrier
[0044] Weigh 2.5 g of the ceramic particle carrier obtained in step (1), 150 g of deionized water, and 12.5 g of 2% by mass dilute hydrochloric acid, mix and place in a hydrothermal reactor, perform hydrothermal reaction at 120° C. for 1 h, filter and place in an oven at 100° C. for 4 h to obtain a modified ceramic particle carrier;
[0045] (3) Preparation of Catalyst
[0046] Weigh 0.126g of cerium nitrate hexahydrate and 0.118g of copper nitrate, dissolve them in 2.52g of deionized water and stir them evenly to obtain an active component precursor mixed solution, then weigh 2g of the modified ceramic particle carrier obtained in step (2) and place it in the active component precursor mixed solution, dry it at 100°C for 3h after impregnation, and then calcine it at 600°C for 2h to obtain a smoldering ceramic-based synergistic denitrification and decarbonization catalyst;
[0047] Based on the mass of the carrier, the mass percentage of the active component is 5%, the mass ratio of the floating beads and Al2O3 in the carrier is 1:1, and the mass ratio of CeO2 and CuO in the active component is 1:1.
[0048] (4) Catalytic activity test
[0049] Take 1mL of 40-60 mesh catalyst and pour it into a quartz tube with an inner diameter of 8mm. Place the quartz tube in a tube furnace and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake components: NO (500ppm), CH4 (500ppm), O2 (11vol.%), and the rest are N2. The total gas flow rate is 500mL / min. The temperature is controlled at 120-300℃, and stays stable for 30min every 30℃. The NO concentration is tested using Laoying 3021 portable carbon emission monitor. At 180-270℃, the NO conversion rate is 100% after 3min (see specific data). Figure 3 ).
[0050] Comparative Example 1
[0051] (1) Preparation of carrier
[0052] Except that 2.5 g of 1% by mass dilute hydrochloric acid was used as an acidifying agent for low-temperature hydrothermal acidification during the catalyst preparation, other conditions were the same as those in Example 1;
[0053] (2) Catalytic activity test
[0054] Take 1mL of 40-60 mesh catalyst and pour it into a quartz tube with an inner diameter of 8mm. Place the quartz tube in a tube furnace and adjust the actual temperature of the catalytic reaction by controlling the heating temperature of the tube furnace. Intake gas components: NO (500ppm), CH4 (500ppm), O2 (11vol.%), and the rest are N2. The total gas flow rate is 500mL / min. The temperature is controlled at 120-300℃, and stays stable for 30min every 30℃. The NO concentration is tested using Laoying 3021 portable carbon emission monitor. At 240℃, the NO conversion rate is 87% after 3min (see specific data). Figure 3 ).
[0055] (3) Contrast effect
[0056] Compared with Example 1, when the amount and concentration of dilute hydrochloric acid are reduced during catalyst preparation, that is, when the amount of acidifier is insufficient, the grain boundaries of the carrier cannot be fully exposed at the microscopic level ( Figure 2 ), and grain boundaries are an important factor in the generation of oxygen vacancies, which leads to reduced catalyst performance; at the macro level, it will cause the water absorption rate of the carrier to decrease, making it difficult for the active components to strongly bind to the carrier surface, and ultimately lead to a decrease in the loading rate of the active components on the carrier surface and easy agglomeration; therefore, compared with Example 1, its catalytic performance is significantly reduced.
Claims
1. A smoldering ceramic-based synergistic denitrification and dehydrogenation catalyst, characterized in that: The catalyst uses ceramic particles made of a mixture of floating beads and Al2O3 as a carrier, a composite oxide of CeO2 and CuO as an active component, and dilute hydrochloric acid as an acidifying agent. It is prepared by a hydrothermal filling-high temperature roasting-low temperature hydrothermal acidification-low temperature roasting method; based on the mass of the carrier, the mass percentage of the active component is 1-10%, the mass ratio of the floating beads to Al2O3 in the carrier is 1:0.1-5, and the mass ratio of CeO2 to CuO in the active component is 1:0.1-5.
2. The catalyst according to claim 1, characterized in that: Based on the mass of the carrier, the mass percentage of the active component is 3-5%, the mass ratio of the floating beads and Al2O3 in the carrier is 1:0.3-1, and the mass ratio of CeO2 and CuO in the active component is 1:0.5-1.
3. A method for preparing the catalyst according to claim 1, characterized in that: The preparation method of the catalyst is as follows: (1) Preparation of ceramic particle carrier Weigh aluminum salt, deionized water and pretreated floating beads, mix them and place them in a hydrothermal stirring kettle, filter and dry them after hydrothermal reaction, and then place them in a high-temperature tube furnace for calcination to obtain a ceramic particle carrier; (2) Modification of ceramic particle carrier The ceramic particle carrier obtained in step (1), deionized water and dilute hydrochloric acid are mixed and placed in a hydrothermal reaction kettle, and after the hydrothermal reaction, the mixture is filtered and dried to obtain a modified ceramic particle carrier; (3) Preparation of Catalyst Weigh cerium salt and copper salt, dissolve them in deionized water and stir evenly to obtain an active component precursor mixed solution, then place the modified ceramic particle carrier obtained in step (2) in the active component precursor mixed solution, immerse and dry and calcine to obtain a smoldering ceramic-based synergistic denitrification and decarbonization catalyst.
4. The method according to claim 3, characterized in that The floating beads pretreatment method is to add fly ash into deionized water, stir and let it stand, filter and dry the ash floating on the surface of the deionized water through overflow, then continue to add the filtered and dried ash into deionized water, stir and let it stand, and obtain the ash on the surface of the deionized water through overflow, and filter and dry for the second time to obtain the pretreated floating beads.
5. The preparation method according to claim 3, characterized in that: The temperature of the hydrothermal reaction in step (1) is 140-160° C., and the time of the hydrothermal reaction is 6-12 h; the stirring rate during the hydrothermal reaction is 40-60 r / min; the drying temperature is 70-100° C., and the drying time is 4-8 h; the calcination temperature is 1200-1400° C., and the calcination time is 8-16 h.
6. The preparation method according to claim 3, characterized in that: The mass ratio of the ceramic particle carrier, deionized water and dilute hydrochloric acid in step (2) is 1:40-60:3-5, and the dilute hydrochloric acid is a hydrochloric acid solution with a mass fraction of 2-10%; The temperature of the hydrothermal reaction in step (2) is 100-120° C., and the time of the hydrothermal reaction is 1-2 hours; the temperature of the drying is 80-100° C., and the time of the drying is 4-8 hours.
7. The preparation method according to claim 3, characterized in that: The cerium salt described in step (3) is cerium nitrate hexahydrate or cerium chloride hexahydrate, and the copper salt is copper chloride or copper nitrate.
8. The preparation method according to claim 3, characterized in that: The drying temperature in step (3) is 80-100° C., and the drying time is 3-6 hours; the calcination temperature is 500-600° C., and the calcination time is 2-4 hours.
9. Use of the catalyst according to claim 1 in the treatment of flue gas during the smoldering process of printing and dyeing sludge.
10. The use according to claim 9, wherein the flue gas is treated by synergistic catalytic purification of hydrocarbons and nitrogen oxides.
Citation Information
Patent Citations
Low-temperature denitration catalyst
CN105032387A
Biomass particle combustion smoke treatment device
CN105903305A
Low-temperature denitration catalyst and preparation method thereof
CN107570142A
Ruthenium-based ultralow-temperature denitration catalyst
CN109718767A
Smoldering treatment and smoke purification device for organic solid waste
CN112097261A